PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) MELALUI PEMBERDAYAAN KARYAWAN DARI BEBERAPA FAKULTAS DI UNIVERSITAS TRISAKTI JAKARTA - Eko Susanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
This research is about “The Effect of Transformational Leadership On Organizational CitizenshipBehavior Mediated by Employee Empowerment Employees On Faculty of Law, Faculty of CivilEngineering and Planning, and Faculty of Landscape Architecture and Technic Environment TrisaktiUniversity Jakarta”. The background of this study is to analyze the factors that can influence theOrganizational Citizenship Behavior Of Employees Faculty of Law, Faculty of Civil Engineeringand Planning, and Faculty of Landscape Architecture and Technic Environment Trisakti UniversityJakarta. The design of this research using primary data obtained by distributing questionnairesto 114 Employees Faculty of Law, Faculty of Civil Engineering and Planning, and Faculty ofLandscape Architecture and Technic Environment Trisakti University Jakarta. Data analysis methodused in this research is Structural Equation Model (SEM). The results of this research concludedthat there is a positive influence on Transformational Leadership against Employee Empowerment,there is a positive influence on the Transformational Leadership against Organizational CitizenshipBehavior, and there is a positive influence on Employee Empowerment against OrganizationalCitizenship Behavior.Keywords: Transformational Leadership, Employee Empowerment, Organizational CitizenshipBehavior